Entrepreneurial sport policy - Ratten, V. (International Journal of Sport Policy and Politics, 2017)
For most sport policy planners, the integration of entrepreneurial initiatives that are practical and relevant to the community is an important way of staying competitive, innovative and forward thinking. Policy regarding sport tries to balance ways to improve financial and social results but facilitate the interest of non-profits and community stakeholders. In addition, with the introduction of more sport policies aimed at increasing tax and other related revenues, there has been an emphasis on innovative policy strategies that go beyond the current status quo and present unique ideas. The aim of this article in this special section is to discuss how the concept of entrepreneurial sport policy can make a contribution to the disciplines of sport management, public policy, entrepreneurship and innovation. This is due to studies of the sport policy process from an entrepreneurial perspective having the prospect of making an interdisciplinary contribution to the literature. As very few studies link the disparate sport and entrepreneurship literature, this article will present a theoretical framework to help understand the importance of taking an entrepreneurial sport policy perspective. Suggestions for policy planners and future research are stated.